Tipos de envase y tiempos de esterilización en el efecto fisicoquímico y microbiológico para pinchagua en conservas de aceite de oliva - Mendoza Tigua, Jonnathan Daniel (2024)
The research was aimed at evaluating packaging types and sterilization times on the physicochemical and microbiological effect of pickles in canned olive oil. Two factors were taken into account, factor A corresponding to packaging types (glass and pouch covers). Meanwhile, factor B at sterilization times (70, 80 and 90 minutes with a temperature of 121°C), a bifactorial arrangement was used in DCA, obtaining six treatments with three replicas; on the other hand, 18 experimental units consisting of 100 g of spilled pinchwater were considered. Variables such as histamine, total volatile basic nitrogen (NBVT), pH and the presence of Clostridium spp. As for the physicochemical results, it was found that histamine levels of 1mg/100g in all studied cases were within the limits permitted by NTE INEN 1772:2013 for canned fish, which establishes a maximum of 5 mg/100g. However, total volatile basic nitrogen (NBVT) levels exceeded established standards (between 57.53 and 75.06) in all treatments, indicating product deterioration. No treatment complied with the above-mentioned regulations. The pH values (between 7.21 and 7.34) also exceeded the standard limit of 6.5. In addition, the presence of Clostridium spp was observed in all treatments, especially in the pouch packaging. This suggests a deterioration of the product in the various sterilization treatments and packaging types evaluated. It is therefore necessary to implement corrective measures to ensure that final products meet established standards and are safe for human consumption.